Pengaruh Jumlah Sel Elektroda Terhadap Produksi Gas Hidrogen dengan Proses Elektrolisis sebagai Sumber Energi Fuel Cell - Erlinawati; Mahesi, Trin Zikir; Saputra, Richo; Febriana, Ida; Effendy A, Sahrul (Talenta Publisher (Universitas Sumatera Utara), 2025)
Hydrogen is an environmentally friendly, carbon-free renewable energy source that can be generated through reactions with oxygen to produce electricity. One method of producing hydrogen is via water electrolysis. The aim of this study was to determine the optimal conditions for hydrogen gas production, specific energy consumption, and the use of hydrogen gas as an energy source for Proton Exchange Membrane (PEM) fuel cells, using potassium hydroxide (KOH) at concentrations of 0.1 M, 0.2 M, 0.3 M, and 0.4 M. The electrolysis process was conducted at a voltage of 10 volts for 30 minutes. The results showed that the highest hydrogen gas production, 0.8927 L, was achieved with 18 electrode cells and a KOH concentration of 0.3 M. The optimal specific energy consumption was 33,269 joules under the same conditions. The maximum efficiency of the PEM fuel cell was 47.25%, while the minimum efficiency was 44.80%